Off to Plan or Out to Lunch? Relationships between Design Characteristics and Outcomes of Strategy Workshops - Healey, Mark P.; Hodgkinson, Gerard P.; Whittington, Richard; Johnson, Gerry (British journal of management, 2015)
Strategy workshops, also known as away days, strategy retreats and strategic ‘off‐sites’, have become widespread in organizations. However, there is a shortage of theory and evidence concerning the outcomes of these events and the factors that contribute to their effectiveness. Adopting a design science approach, in this paper we propose and test a multidimensional model that differentiates the effects of strategy workshops in terms of organizational, interpersonal and cognitive outcomes. Analysing survey data on over 650 workshops, we demonstrate that varying combinations of four basic design characteristics – clarity of goals and purpose, routinization, stakeholder involvement and cognitive effort – predict differentially these three distinct types of outcomes. Calling into question conventional wisdom on the design of workshops, we discuss the implications of our findings for integrating further the strategy process, strategy‐as‐practice and strategic cognition literatures, to enrich understanding of the factors that shape the nature and influence of contemporary strategic planning activities more generally.